ANALISIS YURIDIS TERHADAP REGULASI BPOM DALAM PENGAWASAN JUAL BELI SUSU KENTAL MANIS DENGAN KADAR GULA TINGGI - Rosandi Firmawan; Achmad Fathoni Alfaris; Amzahril Azis; Erviana Resyia (JOURNAL SAINS STUDENT RESEARCH, 2024)
Sweetened condensed milk (SCM) is a popular product in Indonesia; however, it often contains high levels of sugar, which can have adverse health effects. Excessive sugar consumption is associated with health issues such as obesity, diabetes, and heart disease. The Food and Drug Supervisory Agency (BPOM) plays a crucial role in monitoring this product to protect consumers. BPOM regulations concerning the supervision of SCM, such as the Head of BPOM Regulation No. 31 of 2018, govern product labeling, including the prohibition of misleading health claims and the requirement to provide clear information regarding sugar content. Although these regulations exist, their implementation faces challenges, such as limited surveillance and weak enforcement. Misleading marketing and labeling practices still occur, with many producers claiming SCM is a healthy product, especially for children. This contradicts BPOM regulations and has the potential to mislead consumers, particularly parents. Therefore, a juridical analysis of BPOM regulations is essential to ensure consumer protection and strengthen the monitoring of SCM products. This study aims to analyze the effectiveness of BPOM regulations in supervising the sale of SCM and the juridical implications that can be taken to improve consumer protection. Cooperation between BPOM, producers, and the media is needed to enhance public education and strengthen law enforcement to control excessive sugar consumption.